PO.3.53 No evidence of a correlation between serum HCQ concentrations and QTc in SLE. (27th September 2022) - Olsson, A; Tydén, H; Kultima, K; Carlsson, H; Linge, P; Bengtsson, AA; Jönsen, A
Abstract : Objective: The aim of this study was to investigate the relationship between the concentration of hydroxychloroquine (HCQ) in serum and adverse cardiac effects including prolonged QTc interval and cardiomyopathy in patients with systemic lupus erythematosus (SLE) undergoing long-term treatment with HCQ. Methods: The concentration of HCQ in serum from 96 SLE patients treated with HCQ was determined using liquid chromatography – high resolution mass spectrometry. QTc intervals at electrocardiograms were calculated using Bazett's formula. Cardiomyopathy was determined during follow-up in accordance with the SLICC/ACR-damage index definitions. Results: There were 83% women and the median (range) age at study was 47, 5 (21–82) years. As a prerequisite, all 96 SLE patients included in the study were treated with Plaquenil, with 96% stating that they were taking a dose of 200 mg daily. The median (range) duration of treatment was 165, 5 (10–432) months. Median (range) HCQ concentrations in serum were 241 (0–734) ng/mL and mean (±2SD) QTc interval was 416, 8 (±50, 1) ms. In total, 16 patients had QTc ≥440 ms, including one man. Of these patients, five had QTc ≥460 ms. No patient had QTc >500 ms. We found no significant correlation between serum concentrations of HCQ and QTc intervals (r = 0, 175, p = 0, 088) ( Figure 1 ). In the study group, only three patients had evidence of cardiomyopathy. Conclusion: In this study, we could not detect a correlation between serum concentrations of HCQ and prolonged QTc in SLE patients. Low dose HCQ treatment in SLE appears to be safe regarding development of cardiomyopathy.